Vaccination After SARS-CoV-2 Infection Increased Antibody Avidity Against the Omicron Variant Compared to Vaccination Alone - LeMaster, Cas; Geanes, Eric S; Fraley, Elizabeth R; Selvarangan, Rangaraj; Bradley, Todd (The Journal of infectious diseases, 2022)
Abstract The SARS-CoV-2 Omicron variant has caused infections among individuals vaccinated or with prior COVID-19, suggesting immune escape. Here, we showed a decrease in binding and surrogate neutralizing antibody responses to the Omicron variant after 2 doses of the Pfizer COVID-19 mRNA vaccine. Individuals recovered from infection before vaccination had higher antibody levels and avidity to the Omicron variant compared to individuals vaccinated without infection. This suggested that COVID-19 infection before vaccination elicited a higher magnitude and affinity antibody response to the Omicron variant, and repeated exposure through infection or vaccine may be required to improve immunity to emerging SARS-CoV-2 variants. Individuals recovered from COVID-19 had increased magnitude and avidity of the antibody response to the SARS-CoV-2 Omicron variant after vaccination compared to those with no prior infection. Thus, repeated immunization with SARS-CoV-2 spike could increase antibody breadth to emerging variants.